The effect of extended glaze firing on the flexural fatigue strength of hard-machined ceramics - Aurelio, Iana Lamadrid; Prochnow, Catina; Guilardi, Luis Felipe; Ramos, Gabriela Freitas [UNESP]; Bottino, Marco Antonio [UNESP]; May, Liliana Gressler (Elsevier B.V., 2018)
Statement of problem. It is unclear whether an extended glaze firing could improve the long-term mechanical performance of densely sintered CAD-CAM ceramics. Purpose. The purpose of this in vitro study was to analyze the effect of an extended glaze firing on the flexural fatigue strength (FFS) of densely sintered milled (hard-machined) leucite-based (LEU) and lithium disilicate-based (DIS) ceramics. Material and methods. Disks were machined from ceramic blocks and divided into 6 groups (n=20) according to the material, LEU or DIS, and to the applied glaze firing: manufacturer-recommended glaze (G group), extended glaze (EG group), and control/no firing (C group). The surface roughness of the disks was measured before and after firing by using a contact profilometer, and data were compared by paired sample tests. Specimens were submitted to fatigue by using the staircase test design in water (piston-on-3 balls; 500 000 cycles, 20 Hz, and sinusoidal loading). Mean (+/- SD) FFS values were then calculated and analyzed by using 1-way analysis of variance and post hoc Tukey test (alpha=.05). Results. Surface roughness did not change after the firing (P>.05). The highest FFS value in both ceramics was obtained after EG firing (LEU-EG=80.52 +/- 6.3 MPa; DIS-EG=147.25 +/- 10.5 MPa), which was statistically superior to G firing (LEU-G=73 +/- 6.8 MPa, P=.003; DIS-G=134.34 +/- 15.6 MPa; P=.023) and C group (LEU-C=61.94 +/- 63 MPa; P<.001; DIS-C=134.13 +/- 17.3 MPa; P=.023). Conclusions. EG firing optimized the biaxial flexural fatigue strength of hard-machined leucite ceramics compared with conventional glaze firing.